A scalable neighbor-based routing protocol for mobile ad hoc networks - Ejmaa, Ali Mohamed E.; Subramaniam, Shamala; Ahmad Zulkarnain, Zuriati; Mohd Hanapi, Zurina (Hindawi Publishing Corporation, 2016)
Broadcasting is an essential and effective mechanism used to disseminate data on several types of networks such as mobile ad hoc network. Such method is adopted by a considerable number of routing protocols, in particular, in the route discovery stage since the broadcasting is easy to implement and certainly provides an ideal connectivity among nodes. However, the broadcasting increases the routing overhead, packet delay, which negativity affects the throughput due to the excessive use of the redundant Route REQuest message. In addition, the network is susceptible to so-called broadcast storm problem. Therefore, developing a new routing protocol, which is able to relieve the unnecessary Route REQuest messages while boosting the performance of the network, is required. In this article, a novel routing protocol for mobile ad hoc network, called scalable neighbor-based mobile routing, is proposed. The broadcasting in this protocol is governed by the inverse relation between the number of neighbors and the probability of the rebroadcasted Route REQuest messages. Extensive simulation experiments are carried out to evaluate the performance of the proposed protocol and to compare the state-of-the-art protocols, namely, neighbor coverage-based probabilistic rebroadcast, with the latest version of ad hoc on-demand distance vector protocol. Simulation results show that scalable neighbor-based mobile routing outperforms both protocols, the neighbor coverage-based probabilistic rebroadcast and the ad hoc on-demand distance vector, in terms of routing overhead, medium access control collision, end-to-end delay, packet delivery ratio, and energy consumption.